Dynamic Design Analysis Method DDAM - Gene M. Remmers; George J. O’Hara; Patrick F. Cunniff (Shock and Vibration)
This article describes the evolution of the dynamic design analysis method (DDAM) by assimilating information from references spanning more than three decades. This evolution began with attempts to use earthquake engineering practice, circa 1950, in dealing with hostile environments created by modern weaponry. It became necessary to develop new theories that went beyond the then current status. This led to research programs that went back to basic physics and engineering principles that resulted in a sound technique for naval applications. The elements of the technique were theoretically based and confirmed by laboratory and large scale field testing. One important example is the structural interaction effects between a vehicle and large equipment structures by means of a newly defined quantity called modal effective mass. Another example led to the discovery that attaching a vibration generator to a structure in an effort to find the frequencies useful for foundation motion response analysis was guaranteed to produce failure. DDAM continues to be used after its introduction 36 years ago. Although familiar in US and international naval circles, it is not well known by persons other than naval engineers. Many myths and misconceptions have grown during this period, so some of the major ones are addressed.